Photoselective vaporization of the prostate with GreenLight 120-W laser versus transurethral resection of the prostate for benign prostatic hyperplasia: a systematic review with meta-analysis of randomized controlled trials. Issue 2 (February 2016) - Zang, Ya-Chen; Deng, Xin-Xi; Yang, Dong-Rong; Xue, Bo-Xin; Xu, Li-Jun; Liu, Xiao-Long; Zhou, Yi-Bin; Shan, Yu-Xi
Abstract The aim of this study is to assess the overall efficacy and safety of photoselective vaporization of the prostate (PVP) with GreenLight 120-W laser versus transurethral resection of the prostate (TURP) for treating patients of benign prostate hyperplasia (BPH) with lower urinary tract symptoms (LUTS). We performed a literature search of The Cochrane Library and the electronic databases, including Embase, Medline, and Web of Science. Manual searches were conducted of the conference proceedings, including European Association of Urology and American Urological Association (2007 to 2012). Outcomes reviewed included clinical baseline characteristics, perioperative data, complications, and postoperative functional results, such as postvoid residual (PVR), international prostate symptom score (IPSS), quality of life (QoL), and maximum flow rate (Qmax ). Six randomized controlled trials (RCTs) were enrolled. Three hundred and forty-seven patients undergone 120-W PVP, and 350 patients were treated with TURP in the RCTs. There were no significant differences for clinical characteristics in these trials. In perioperative data, catheterization time and length of hospital stay were shorter in the PVP group. However, the operation time was shorter in the TURP group. Capsular perforation, blood transfusion, clot retention, and macroscopic hematuria were markedly less likely in PVP-treated subjects. The other complications between PVP and TURP did not demonstrate a statistic difference. There were no significant differences in QoL, PVR, IPSS, and Qmax in the 1, 3, 6, 12, and 24 months of postoperative follow-up. There was no significant difference at postoperation follow-up of functional outcomes including IPSS, PVR, Qmax, and QoL between the TURP-treated subjects and PVP-treated subjects. Owing to a shorter catheterization time, reduced hospital duration and less complication, PVP could be used as an alternative and a promising minimal invasive surgical procedure for the treatment of BPH.